Research handbook on design law - Hartwig, Henning (Research handbooks in intellectual property, 2021)
"Written by expert scholars and practitioners, this unique Research Handbook presents the state of the art in research on, and the practice of, international design law. Combining cutting edge research with a practical approach, it examines key trends and covers key cases, regional and national laws, as well as concepts of international design protection. In particular, the U.S. framework is compared with the regime of the EU, and issues relating to the Hague Agreement are also covered. Split across five thematic parts, this Research Handbook examines the foundations of, and methodological perspectives on, design law, the establishment and enforcement of protection, as well as many other critical issues, addressed from a transnational and comparative approach. Chapters consider protection of three-dimensional trademarks, graphical user interfaces, spare parts, protection of designs on the basis of use, priority issues under the Community design scheme, and cross-border copyright protection in Europe. Clear and accessible, the Research Handbook on Design Law will be of value to emerging and established scholars and students of international design law, while also being a key resource for practitioners and policy makers seeking to react and adapt to the rapid emergence of global developments"--